Flight‐initiation response reflects short‐ and long‐term human visits to remote islets. (3rd January 2020) - Thibault, Martin; Weston, Michael A.; Ravache, Andreas; Vidal, Eric
Abstract : The increasing use of, and visits to, isolated territories by people (especially tourists) enables the investigation of how biodiversity reacts to evolutionarily novel pressures. We explored the behavioural reaction of a breeding seabird species, the Brown Noddy Anous stolidus, to our repeated visits at two study sites in the Chesterfield Islands, a newly classified reserve in the Coral Sea Natural Park. Repeated measures of flight‐initiation distances (FIDs) at three sites and over time suggest that human visitations induced both a spatial phenotypical sorting or learning of individuals and a temporal habituation. In light of the novel 'Sit and Defend' mode of avian nest defence, the study finally provides the first dataset of FIDs for this species, and highlights management opportunities that could arise from the replication of such an approach to other breeding seabirds and therefore the conservation of remote island ecosystems.